Subjectivity in the assessment of learning (Research, Society and Development, 2021)
The objective of this study was to verify whether or not subjectivity can influence learning assessment, including interfering in the student's progression to later grades. The research was carried out through bibliographic studies, where data were collected and interpreted in articles, books, academic works and other scientific texts. As a result, it was verified about the teacher education regarding the learning evaluation, as well as identified the historical context and the concepts about evaluation. Finally, the relationships between subjectivity, learning and evaluation were analyzed. As a conclusion, it was observed that subjectivity is present not only in the learning assessment process, but in every educational environment, as it is an inherent part of the individuals that compose it. And with the teacher it would not be different, since it is necessary to be aware of subjectivity during the corrections of the activities developed by the students, in order to try to minimize it so as not to harm the students.